The Role of Micro Small Medium Enterprises (MSMEs) In Halal Industry Enhancement (Case Study of MSMEs in Lhokseumawe – Aceh) - Rani Puspitaningrum; Damanhur Damanhur; Falahuddin Falahuddin; Ahmad Fauzul Hakim Hasibuan; Selvia Agustin (Universitas Pendidikan Indonesia, 2021)
AbstractPurpose – This study examined the role of MSMEs in encouraging the halal industry and aimed to determine the problems of MSMEs in supporting the halal industry in Lhokseumawe..Methodology - This study used primary data of qualitative study with descriptive data analysis from five interviewees as an owner of food and beverage MSMEs sector in Lhokseumawe-Aceh. The research method used is a case study approach. Data collection techniques used were interview, observation, and documentation, and data analysis techniques used in this study with data reduction, data presentation, conclusion, and triangulation stages. Findings - The results showed that the role of MSMEs in encouraging the halal industry was relatively low due to the lack of knowledge and awareness of MSME actors in Lhokseumawe city about halal certification that provides services to MSMEs.Keywords: Islamic Economics, Micro Small Medium Enterprises (MSMEs), Halal Industry, Qualitative Method, Consumer Satisfaction